Rancang Bangun Saron Digital (Laron) Berbasis Capacitive Sensor Pada Arduino Uno - retno wahyusari; Lastoni Wibowo (SIMETRIS, 2018)
Blora Regency has a diverse artistic treasury. Various arts have been preserved until now. Besides attracting tourists to Blora, the art is also a manifestation of the high creativity of Blora people. The five distinctive arts of Blora Regency that are still preserved by the community are: Barongan Blora, Tayub Blora, Kadroh, Ketoprak, and Karawitan. Almost all of the typical arts of Blora Regency use gamelan instruments. Gamelan itself is a musical instrument not only owned by Blora Regency, but also an Indonesian traditional musical instrument that is worldwide. Gamelan for ancient people is considered as their identity, according to them traditional music is something to be proud of and liked. But why do young people today even dislike traditional music. One effort to attract the interest of the younger generation is to modernize the gamelan. Modernizing gamelan is not only to attract the interest of the younger generation, it will also be used as a solution to of preserving culture. Keywords: Arduino Uno, Capasitive Sensor, Saron Digital